Temporary interference in human lateral premotor cortex suggests dominance for the selection of movements. A study using transcranial magnetic stimulation. - Schluter, N; Rushworth, M; Passingham, R; Mills, K (1998)
It is known that damage to the left hemisphere can lead to movement deficits, and that patients with apraxia have difficulty in selecting movements. Neurophysiological recording studies and lesion studies have shown that the premotor cortex is important for the selection of movements in monkeys. In this study we used transcranial magnetic stimulation (TMS) to disrupt the processing in human premotor cortex. We applied TMS to normal healthy volunteers over the premotor and primary motor areas while they carried out choice reaction time and simple reaction-time tasks. We measured response times of either hand as subjects were stimulated over the left and right hemisphere separately. We found that we were able to delay responses by stimulating at short cue-stimulus intervals (100-140 ms) over premotor cortex and at longer cue-stimulus intervals (300-340 ms) over primary motor cortex while subjects performed the choice reaction-time task with the contralateral hand. We were also able to delay responses with the ipsilateral hand while stimulating over the left premotor cortex, but not while stimulating over the right premotor cortex or either sensorimotor cortex. Premotor cortex stimulation alone disrupts an early stage of movement selection; motor cortex stimulation disrupts the movements at a later stage of execution. There was no distinguishing short cue-stimulus interval effect when premotor cortex was stimulated in the simple reaction time paradigm, where the movement selection demands of the task are kept to a minimum. We conclude that the premotor cortex is important for selecting movements after a visual cue and that the left hemisphere is dominant for the rapid selection of action.